Change of direction deficit and maximum deceleration variations between different age groups in academy soccer players - Adams, L.; Thomas, K.; Newton, J. (The Journal of Strength and Conditioning Research, 2021)
Change of direction (COD) and linear sprint qualities are integral for team sport athletes, occurring during key moments within matches (i.e., scoring). One factor influencing COD ability is maturation, as the onset of adolescent awkwardness around peak height velocity might negatively affect performance of skilled, coordinative tasks; specifically, the ability to accelerate, decelerate and change direction, while effecting physical qualities such as eccentric strength. Purpose: The purpose of this study was to examine COD performance and linear acceleration and deceleration capabilities between different age groups in academy football players. Methods: Twenty-three academy soccer players (U18:n = 5,U16:n = 9 and U15:n = 9) performed 2 max effort modified 505 (M505) for both limbs, and three 40 m max sprints, with a 10 m split time (acceleration). Max deceleration performance was assessed by having the athletes stop in the shortest distance possible following the 40 m sprints. All times were recorded via electronic timing gates (Browser Timing systems, Draper) placed 2 m apart at hip height. Subjects started 1 m behind the first timing gates, with a two-point staggered stance with no countermovement. A tape measure was placed from the 40 m mark, with an athlete's distance marked for each deceleration. Three minutes of recovery was provided between each rep. A standardised warm up was performed prior to testing. Change of direction deficit (CODD) was calculated using the formula: 505 time—10 m sprint time. Mean and SD was calculated for all variables. A Shapiro Wilks test was used to assess normality. Absolute and relative reliability was measured with coefficients of variation (CV) and an interclass correlation coefficients (ICCs). A one-way-between-subject non-parametric ANOVA (Kruskal Wallace), with Bonferroni-adjusted pairwise comparisons and Hedge's g effect sizes were calculated. Results: All measures achieved acceptable reliability (CV = 0.271-1.93, ICC >0.74), except maximum deceleration stopping distance (CV = 13.5, ICC = 0.58). The U18 players were, faster than the younger age groups for all test, albeit non-significant, trivial-moderate in magnitude. However, CODD could not discriminate between age groups (p = 0.61-1.00, g = 0.11-0.61) (Figure 1). For maximal deceleration, the U15 s were significantly greater than the U18 s (p = 0.05, g = 0.79), with a non-significant trivial difference between U18 s vs. U16 s (p = 1.00, g = 0.02). The U15 s were also greater than the U16 s, albeit non-significant (p = 0.06, g = 0.81). Conclusions: The oldest age group i.e., U18's, had a greater linear speed and COD performance compared to younger athletes, but not for CODD or maximal deceleration. Practical Applications: For COD performance, both CODD and total performance time should be observed. As across age groups CODD did not change despite improvements in linear sprint qualities and M505 total performance time which would be more relevant for sports performance.